The Influence of Social Change on Gender Roles in Society: A Civil Law Perspective - Nur Hakima Akhirani Nasution; Amru Hasibuan; Erwin Hamonangan Pane (Inovasi Pratama Internasional. Ltd, 2023)
This research aims to analyze the influence of social change on gender roles in society from a civil law perspective. The research method used is literature study by collecting data from various sources such as books, journals and related articles. The research results show that social changes influence gender roles in society, especially in terms of rights and obligations in civil law. Social changes such as technological advances, globalization, and changes in social values affect gender roles in society. The conclusion of this research is that social changes influence gender roles in society and efforts are needed to adapt civil law to these social changes.